2020
DOI: 10.3390/antiox9010045
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Proliferative and Anti-Invasive Effect of Leaf Extracts of Blueberry Plants Treated with Methyl Jasmonate on Human Gastric Cancer In Vitro Is Related to Their Antioxidant Properties

Abstract: Gastric cancer is the third main cause of cancerous tumors in humans in Chile. It is well-accepted that a diet rich in antioxidant plants could help in fighting cancer. Blueberry is a fruit crop with a high content of antioxidants. Methyl jasmonate (MeJA) is a phytohormone involved in plant defenses under stress conditions. The exogenous application of MeJA can improve the antioxidant properties in plants. We studied in vitro and in vivo anticancer action on human gastric cancer (cell line AGS) and the antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 76 publications
1
29
0
Order By: Relevance
“…These authors indicated that the greatest inhibitory activity was found in the anthocyanin fraction, with a 50% inhibition of cellular proliferation, concluding that the blueberry intake could reduce the colon cancer risk. Accordingly with our results, Ribera-Fonseca et al (2020) reported that anthocyaninrich extracts of highbush blueberry significantly decreased A G S c e l l v i a b i l i t y b y a r o u n d 2 0 -3 0 % a t 100 μg mL −1 compared to the negative and positive control (quercetin 4 μM). Peiffer (2018) pointed out that the preparation of fractions possessing enriched amounts of the active constituents of Black Raspberry, including anthocyanins, protocatechuic acid, quercetin, ellagic acid (all of which have exhibited anti-cancer properties), may improve patients' access to the anti-cancer benefits afforded by this species.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…These authors indicated that the greatest inhibitory activity was found in the anthocyanin fraction, with a 50% inhibition of cellular proliferation, concluding that the blueberry intake could reduce the colon cancer risk. Accordingly with our results, Ribera-Fonseca et al (2020) reported that anthocyaninrich extracts of highbush blueberry significantly decreased A G S c e l l v i a b i l i t y b y a r o u n d 2 0 -3 0 % a t 100 μg mL −1 compared to the negative and positive control (quercetin 4 μM). Peiffer (2018) pointed out that the preparation of fractions possessing enriched amounts of the active constituents of Black Raspberry, including anthocyanins, protocatechuic acid, quercetin, ellagic acid (all of which have exhibited anti-cancer properties), may improve patients' access to the anti-cancer benefits afforded by this species.…”
Section: Discussionsupporting
confidence: 88%
“…On this basis, it has been suggested that they could be potential therapeutic tools against the co-morbidity associated with the development of obesity. Lately, Ribera-Fonseca et al (2020) found that leaf extracts of highbush blueberry at a concentration equal or higher than 400 μg mL −1 caused more than 50% of AGS cell viability inhibition, reaching 60% of inhibition at the highest doses studied (3200 μg mL −1 ). In contrast, fruit extract provoked only about 10% of inhibition of AGS cell viability at extract exposure during 48 h at the highest concentrations (1600 μg mL −1 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations